The circRAB3IP Mediated by eIF4A3 and LEF1 Contributes to Enzalutamide Resistance in Prostate Cancer by Targeting miR-133a-3p/miR-133b/SGK1 Pathway - Chen, Dong; Wang, Yaqin; Yang, Feiya; Keranmu, Adili; Zhao, Qingxin; Wu, Liyuan; Han, Sujun; Xing, Nianzeng (Frontiers in Oncology, 2021)
An increasing number of studies have shown that circRNAs are closely related to the carcinogenesis and development of prostate cancer (PCa). However, little is known about the effect of the biological functions of circRNAs on the enzalutamide resistance of PCa. Through bioinformatic analysis and experiments, we investigated the expression pattern of circRNAs in enzalutamide-resistant PCa cells. Quantitative real-time PCR was used to detect the expression of circRAB3IP, and plasmids that knock down or overexpress circRAB3IP were used to evaluate its effect on the enzalutamide sensitivity of PCa cells. Mechanistically, we explored the potential regulatory effects of eIF4A3 and LEF1 on the biogenesis of circRAB3IP. Our in vivo and in vitro data indicated that increased expression of circRAB3IP was found in enzalutamide-resistant PCa, and knockdown of circRAB3IP significantly enhanced enzalutamide sensitivity in PCa cells. However, upregulation of circRAB3IP resulted in the opposite effects. Further mechanistic research demonstrated that circRAB3IP could regulate the expression of serum and glucocorticoid-regulated kinase 1 (SGK1) by serving as a sponge that directly targets miR-133a-3p/miR-133b. Then, we showed that circRAB3IP partially exerted its biological functions via SGK1 signaling. Furthermore, we discovered that eIF4A3 and LEF1 might increase circRAB3IP expression in PCa.